Complexity in vocational education and training governance - Oliver, Damian [Verfasser] (My University, 2010)
"Complexity is a feature common to all vocational education and training (VET) governance arrangements, due to the wide range of students VET systems caters for, and the number of stakeholders involved in both decision making and funding and financing. In this article, Pierre and Peter's framework of governance is used to examine complexity in VET governance models. Criticism has been made of complex decision-making processes in VET governance models, whether stemming from co-determination with social partners or shared responsibilities in federations between national and sub-national governments, with the contention being that such complex processes reduce system adaptability. This article argues that the focus on decision-making processes is misguided and the effects of other complex system processes should be considered. First, debate needs to be broadened to take into account how governance frameworks emerge from historical and political differences, such as the impact of federal structures of government. Adaptability depends on more than decision-making processes. Second, international comparisons suggest that complex policy instruments, whether the result of convoluted decision-making or not, may demonstrate greater adaptability in the system but also threaten system coherence. Finally, complex processes for allocating resources and generating feedback seem to increase system accountability, although unintended consequences for other system outcomes may yet emerge." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; T 1.5 International vergleichende Berufsbildungsforschung; Berufsbildung; Berufsbildungspolitik; Bildungssteuerung; Kompetenzverteilung; Bundesregierung; Sozialpartner; Landesregierung; Internationaler Vergleich